Automated Odour Measurement In Electronic Nose System Using Microcontroller. - Noorsal, Emilia; Sidek, Othman; Mohamad Saleh, Junita (2006)
This paper presents an automated odour measurement process using AT89C55WD Microcontroller for the electronic nose (e-nose) system.